2021
DOI: 10.1002/aic.17490
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar membrane electrodialysis for clean production of L‐10‐camphorsulfonic acid: From laboratory to industrialization

Abstract: In this study, bipolar membrane electrodialysis (BMED) was implemented for cleaner production of L-10-camphorsulfonic acid (L-CSA) to lower the environmental impact.Under the current density of 300-400 A/m 2 and feed salt concentration of 6-10 wt. %, the energy consumption and current efficiency were 2.24-2.70 kWh/kg and 20.89-29.5%, respectively. Positron annihilation lifetime spectroscopy, x-ray photoelectron spectroscopy with ion beam etching, and other characterizations were used to elucidate the transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…The similar phenomenon was also observed in our previous study. 5 Meanwhile, it could be observed that the voltage drop of various membranes follows the order of CMX > CJMC-3 > TWEDC > CJMC-5. This trend is generally consistent with the observed area resistance of those cation-exchange membranes as listed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The similar phenomenon was also observed in our previous study. 5 Meanwhile, it could be observed that the voltage drop of various membranes follows the order of CMX > CJMC-3 > TWEDC > CJMC-5. This trend is generally consistent with the observed area resistance of those cation-exchange membranes as listed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…This trend is consistent with numerous studies. 5,8,27 A higher current density resulted in a less ratio of the NaOH migrating out of the base compartment due to the concentration gradient. Therefore, the current efficiency increased steadily at high current densities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bipolar membrane electrodialysis (BMED), an environmentally friendly technique that enables the conversion of salts into the corresponding acids and bases, creates possibilities for the avoidance of the vanadium ammonium precipitation procedure. By taking advantage of intensive water splitting in the bipolar membrane under a reverse bias, the BMED technique has gained great commercial interest and is widely used for a variety of applications such as acid/base production, cleaner production, environmental protection, and CO 2 reduction, , among others. However, to the best of our knowledge, there are no studies that investigate the preparation of vanadium oxide using the BMED technology. Compared with common inorganic salts, vanadium is a group VB element.…”
Section: Introductionmentioning
confidence: 99%